Digital Innovation and Firm Environmental Performance: The Mediating Role of Supply Chain Management Capabilities - Wang, Mengmeng; Teng, Wei (Frontiers in Psychology, 2022)
Given the omnipresence and profoundness of the ongoing pandemic from the Coronavirus disease 2019, its potential spread can be minimized through social distancing. However, this practice causes increasing difficulties and undesirability of traditional transactions or interactions. Accordingly, various manufacturing firms around the world have become more committed not only to accelerating the development of digital technologies, but also to integrating them with existing processes. In this study, we address an important issue of how manufacturing firms can adapt to the ever-changing volatility and unpredictable global business environment, and achieve sustainable growth by developing a strong supply chain management capability. Two specific interrelated research questions are considered: 1) How do supply chain management capabilities contribute to firm environmental performance; and 2) What are the sources of such capabilities? In so doing, we integrate various forms of digital innovation into a supply chain management capability logic to explore their antecedents and consequences. By using survey data from 272 manufacturing firms in China, we examine the relationship between three key forms of digital innovation (i.e., product, platform, and service) and firm environmental performance. Results show that digital product, platform, and service innovations all have positive contributions to supply chain management capability. In turn, supply chain management capabilities have a partial mediating effect between digital product innovation and firm environmental performance, but a full mediating effect between digital platform and service innovations and firm environmental performance.